Features of the 4- dimethylaminobenzoylhydrazone ethyl ester of 2.4-dioxopentanoic acid - Ro`ziyeva, Maftuna (Центр Научных Публикаций (buxdu.uz), 2024)
The composition and structure of 4-dimethylaminobenzoylhydrazone ethyl ester of 2,4-dioxopentanoic acid (I) were established by elemental analysis, IR and 1H-NMR spectroscopy. The resulting ligand single crystals were studied by X-ray diffraction analysis. Thus, as a result of IR, NMR-1Н, and X-ray studies, it was found that the compound I in the solid state is in the pyrazoline ring IC. In the crystal structure, the organic molecules are linked with the intermolecular O–H···O, C–H···O hydrogen bonds as well as C–H··· π and π−π interactions which form 3D crystal structures and ensure the lattice stability. Hirshfeld surface analysis indicates that the most important contributions to the crystal packing stem from H…H (58.2%), H…O/O…H (19.5%) and H…C/C…H (14.9%) interactions. Energy framework calculations reveal a significant contribution of dispersion energy. The calculated highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy gap is 4.522 eV.